Relationship Between Knowledge and Parctice of Mothers With Basic Immunization Completeness in Infant Aged 0-12 - Umi Widyaningsih (JURNAL KEBIDANAN, 2022)
Background: Based on the Health Profile of Kediri Regency, immunization coverage in 2015, Kediri Regency has not reached the predetermined terget because the coverage is still below 90%. According to the reporting that has been collected in the Kediri District Health Profile, the Papar District is one of the three sub district that has the lowest proportion of immunization coverage, which is below 80%. Aim: This study is conducted to determine the relation between mothers’ knowledge and practices and basic immunization completeness coverage on babies aged 0-12 months in Papar District Health Center, Kediri Regency. Method: This study uses observational analytical study with cross sectional approach. The population were all mothers who have babies aged 0-12 months in the Papar District, Kediri Regency, amounting to 416. Moreover, this study uses total sampling technique to gather the data. The instrument used for this study cinsisted of two questionnaires, a questionnaire for knowledge and practice. Results: The sample size was 150 respondents with the inclusion criteria including mothers that have babies aged 0-12 months, are at the location at the time of this study, and are willing to be respondents. Meanwhile, the exclusion criteria are mothers who do not have MCH Handbook (Kartu Ibu dan Anak/KIA) or growth chart (Kartu Menuju Sehat/KMS) and mothers who are out of town when the data collection is conducted. It is shown that 48% of mothers have good knowledge, 93.3% of mothers have good practices towards immunization, and 92% of infants had complete immunization coverage. The results of the Chi-square test of knowledge on immunization completeness coverage p = 0.527 (p>0.05), practice on immunization completeness coverage p = 0.001 (p <0.05). Conclusion: The data shows that there is no relationship between knowledge and immunization completeness coverage. Meanwhile, it is found that there is a relationship between practice and immunization completeness coverage in Papar District Health Center, Kediri Regency.